PUNCTUALITY DELIVERY OF EXPORT CARGO VIA SEA TRANSPORT TO PERFORMANCE OF EMPLOYEE AT LOGISTICS AND FREIGHT FORWARDING COMPANY - Nita Rosmala Dewi; Voni Anisa Meidina; D.A Lasse (Institut Transportasi dan Logistik Trisakti, 2017)
The purpose of this study was to determine the cause of delay cargo and its effect on employee performance. Some business owners in Indonesia, conduct export and import that aims to expand its business branch or to obtain raw materials that are not available in the country to obtain higher quality products. Transportation is the transfer of people or goods from one place to another by using a vehicle driven by man or machine. Sea transport has been chosen by the business owners to send raw materials and finished goods belong to them. Nowadays, demand of export cargo by sea is increase, because shipping cargo using sea transport gives an affordable cost and has a greater capacity than other transport. The writer analyzes the influence of punctuality delivery of export cargo to the level of employee performance in PT Schenker Petrolog Utama, Surabaya branch. The writer used a simple linear regression method with quantitative approach to see the influence and between variables. The result of this research is by 43,4% delay cargo affected the performance of employees, and by 56,7% affected by other factors.